The risk and protective factors associated with depression and anxiety in a national sample of Irish adolescents. (9th January 2015) - Dooley, B.; Fitzgerald, A.; Giollabhui, N. M.
Abstract : Objectives: The aim of this study is to examine the risk and protective factors associated with anxiety and depression in a representative sample of Irish adolescents. Methods: Data used in this study were drawn from a subset of the My World Survey (MWS). The MWS-Second Level (MWS-SL) subset consists of a randomised sample of 72 schools, with a final sample of 6085 students. Outcome measures were depression and anxiety. Risk and protective factors included measures within the socio-demographic, psychosocial and risk-taking domains. Results: One in three adolescents experienced elevated levels of depression and anxiety. Age, gender, maternal education, family composition, parental mental health as well as the experience of racism and bereavement were associated with elevated distress. Psychosocial factors associated with depression and anxiety included optimism, personal competence, life-satisfaction, self-esteem, anger, body dissatisfaction, family competence, maternal and paternal criticism, experiencing the break-up of a romantic relationship, school and peer connectedness as well as the availability of one good adult. Finally, engaging in substance misuse was found to increase the likelihood of anxiety and depression. Conclusion: Since factors protecting and putting adolescents at risk of anxiety and depression exist at every level of the adolescent's ecological system, the study supports a community-based approach to youth mental health.